Comparison of Clinical Outcomes Between Fluoroscopic and Computer Tomographic Guidance in Concurrent Use of Radiofrequency Ablation and Vertebral Augmentation in Spinal Metastases: A Scoping Review - Qing Zhao Ruan; Syena Sarrafpour; Jamal Hasoon; R. Jason Yong; Christopher L. Robinson; Matthew Chung (Diagnostics)
Background/Objectives: The image guidance of choice for the combination therapy of radiofrequency ablation (RFA) and vertebral augmentation (VA) in the context of vertebral disease from spinal metastases are fluoroscopy and computer tomography (CT). Here, we aimed to assess the roles of both imaging modalities and if adoption of either would influence clinical outcomes of pain, physical function, and quality of life (QoL). RFA has been favored as a minimally invasive option for managing painful spinal metastases, and it is often coupled with VA to treat underlying osseous structural instability. This combination therapy of RFA with VA, which could be performed under CT or fluoroscopy, has in recent years been recognized as highly successful for pain control and functional restoration of metastatic spine lesions. Methods: Our scoping review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The databases accessed were Medline and Embase, and the time frame of the search was set from database inception to 2 January 2025. The inclusion eligibility included primary research studies utilizing clearly defined imaging modalities of interest with measurable clinical end points of pain, quality of life (QoL), analgesic use, or complications. Results: Twenty-two articles were identified after screening fifty-eight papers using the databases. Fluoroscopy alone was the more frequently adopted imaging modality (n = 17/22, 77.3%). Almost all of the papers, regardless of the imaging modality used, consistently demonstrated reduction in pain, improvement in QoL, as well as a decrease in analgesia use. Complications were present but had minimal clinical implications, aside from a single article which appeared to demonstrate significantly higher cement leak rates with a singular case of resultant paraplegia. Conclusions: Fluoroscopy- and CT-guided RFA with VA have both proven to be efficacious in reducing patient discomfort and improving functionality while keeping risks of permanent neurological injuries to a minimum.